Sustainability experiments in Asia: Innovations shaping alternative development pathways? - Frans Berkhout (2018)
Global sustainability is increasingly influenced by processes of industrialisation and urbanization in non-OECD countries, especially in Asia. Growth models suggest that developing economies and regions will become first relatively more resource- and pollution-intensive, before converging on more resource-efficient and low-pollution production and consumption patterns expressed in developed countries. Alternative less resource- and pollution-intensive growth models for latecomer countries promise social and economic benefits in the short- and long-term. Drawing on insights from system innovation research on long-run change in socio-technical systems, we discuss the potential role of 'sustainability experiments' to generate innovations that will constitute new 'greener' growth models. We observe a great number of technology-based initiatives that we characterize as sustainability experiments in East and South Asian countries. These experiments emerge in the context of the growth of new socio-technical regimes in key sectors, including energy, transport, manufacturing, food and the built environment. We set out a conceptual framework for assessing the role of experiments, and for evaluating how they link with and become anchored into alternative more sustainable regimes. In this paper we argue that sustainability experiments represent a significant new source of innovation and capability-formation, linked to global knowledge and technology flows, which could reshape emergent socio-technical regimes and so contribute to alternative development pathways in latecomer countries. We conclude by summarizing the six papers published in this Special Issue. © 2010.